Agreement between cerebrospinal fluid biomarkers, brain 18-Fluorodeoxyglucose PET, and clinical diagnosis in older adults with cognitive impairment - Alberto J. Mimenza-Alvarado; Karen G. León-; Rodrigo Hernández-Ramírez; Juan de D. Rodríguez-Callejas; Sara G. Yeverino-Castro; Sara G. Aguilar-Navarro (Permanyer, 2024)
Background: Clinical practice has advanced toward a combined diagnostic approach that involves clinical criteria and biological markers for Alzheimer's disease (AD) and other dementias. Objective: To establish the level of diagnostic agreement between an initial clinical diagnosis and cerebrospinal fluid (CSF) and [18F]-fluorodeoxyglucose (FDG)-positron emission tomography (PET) biomarkers in a cohort of patients from a memory clinic. Methods: This is a observational, retrospective, cohort study conducted at an outpatient memory clinic. Between July 2018 and September 2023, data from adults' ≥ 55 years with a mild cognitive impairment or dementia diagnosis without etiological diagnosis were obtained, complemented with the evaluation of biomarkers in CSF and [18F] FDG-PET biomarker assessment were included. Kappa coefficients (κ) were used to establish the level of agreement between CSF and [18F] FDG-PET results. Results: Seventy-seven patients had an available [18F] FDG-PET scan, and 25 (32.5%) had both biomarkers. We observed a fair-to-moderate diagnostic agreement between patients' initial and their final diagnosis in the presence of CSF (κ = 0.233, 95% confidence interval [CI]: −0.099-0.566) and [18F] FDG-PET (κ = 0.451, 95% CI: 0.277-0.625, p < 0.001) results. The Kappa value for diagnostic concordance between [18F] FDG-PET and CSF to differentiate between AD and other dementias was 0.733 (95% CI: 0.425-1.000, p < 0.005). Conclusion: This study demonstrates good agreement between the CSF and FDG-PET biomarkers to differentiate AD from other dementias.